Penyalahgunaan Yang Sering Terjadi Dalam Pemanfaatan Teknologi Informasi dan Transaksi Elektronik. - Nining Yurista Prawitasari, S.H.,M.H.; Novitria Haryani; Rizki Aulia Rohmat (JURNAL HUKUM PELITA, 2022)
The development of information and communication technology has an important role in human life, especially the Indonesian people, both now and in the future. The progress of the times requires entrepreneurs to develop their business through e-commerce which currently plays a role as a driving force for the Indonesian economy. In addition to e-commerce or electronic transactions, many social media also occupy popularity among the Indonesian people. However, as information and communication technology advances, the threat of internet-based crime is also getting bigger. Therefore, in Indonesia, UU ITE was formed which aims to protect the public in the use of information and communication technology.